A FOUNDATION FOR DEVELOPING SUSTAINABLY SECURE SYSTEMS. Issue 2 (July 2016) - Khou, Stephen; Mailloux, Logan O.; McEvilley, Michael
ABSTRACT: This article is intended to introduce and familiarize systems engineers with ongoing developments in the field of systems security engineering and particularly the effort to develop NIST Special Publication 800‐160 Systems Security Engineering, which provides security considerations for engineering trustworthy secure systems.